Investigation of SHOX Gene Mutations in Turkish Patients with Idiopathic Short Stature - DELİL, KENAN (GALENOS YAYINCILIK, 2016)
Objective: The frequency of mutations in the short stature homeobox (SHOX) gene in patients with idiopathic short stature (ISS) ranges widely, depending mostly on the mutation detection technique and inclusion criteria. We present phenotypic and genotypic data on 38 Turkish patients with ISS and the distinctive features of 1 patient with a SHOX deletion. Methods: Microsatellite markers (MSMs) DXYS10092 (GA repeats) and DXYS10093 (CT repeats) were used to select patients for fluorescent in situ hybridisation (FISH) analysis and to screen for deletions in the SHOX gene. The FISH analysis was applied to patients homozygous for at least one MSM. A Sanger sequencing analysis was performed on patients with no deletions according to FISH to investigate point mutations in the SHOX gene. Results: One patient (2.6%) had a SHOX mutation. Conclusion: Although the number of cases was limited and the mutation analysis techniques we used cannot detect all mutations, our findings emphasize the importance of the difference in arm span and height when selecting patients for SHOX gene testing.
Keywords: Idiopathic short stature; SHOX gene; pseudoautosomal region 1; height; arm span-height difference; LERI-WEILL DYSCHONDROSTEOSIS; GROWTH-HORMONE; DELETIONS; HOMEOBOX; CHILDREN; DEFICIENCY; PHENOTYPES; FAILURE